CONFLICT TRANSFORMATION THROUGH DIGITAL MEDIATION: A STUDY OF BRAZIL'S JUDICIARY COURTS - Curbage, Fernanda (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2023)
This study aims to examine the characteristics of online mediation within public systems, focusing on two pivotal elements: the technological progression instigated by the Covid-19 pandemic that led to an almost full digitalisation of Brazil's judicial system and the subsequent implications of an emancipatory conflict transformation. The research engages social constructivist ontological and epistemology of the south as perspectives, thereby conducting an empirical inquiry into the modifications, aspects, and efficacy of mediation across two judicial districts in São Paulo, Brazil, specifically the cities of Piracicaba and Campinas. The paper underscores the role of mediation within the sphere of online dispute resolution (ODR) in Brazil's legal system, serving to enhance access to justice, expedite communicational changes, and address the limitations of digital mediation while ensuring the active involvement of all parties in the proceedings.Furthermore, the study critically assesses and evaluates the use of mediation as a vital tool in national and international legal systems during the digital judiciary age. To achieve this, a comprehensive re-evaluation of the core principles of mediation is undertaken and juxtaposed with the challenges observed in these regional settings, thus unearthing various topics that necessitate further exploration. In summation, this study offers an insightful understanding of the modalities and regional practices of digital communication in mediation, positing it as a trailblazing approach to enhancing the efficacy of conflict resolution practices and furthering social, cultural, and academic transformation.